Pulseq‐CEST: Towards multi‐site multi‐vendor compatibility and reproducibility of CEST experiments using an open‐source sequence standard. Issue 4 (7th May 2021) - Herz, Kai; Mueller, Sebastian; Perlman, Or; Zaitsev, Maxim; Knutsson, Linda; Sun, Phillip Zhe; Zhou, Jinyuan; van Zijl, Peter; Heinecke, Kerstin; Schuenke, Patrick; Farrar, Christian T.; Schmidt, Manuel; et al.
Abstract : Purpose: As the field of CEST grows, various novel preparation periods using different parameters are being introduced. At the same time, large, multisite clinical studies require clearly defined protocols, especially across different vendors. Here, we propose a CEST definition standard using the open Pulseq format for a shareable, simple, and exact definition of CEST protocols. Methods: We present the benefits of such a standard in three ways: (1) an open database on GitHub, where fully defined, human‐readable CEST protocols can be shared; (2) an open‐source Bloch‐McConnell simulation to test and optimize CEST preparation periods in silico; and (3) a hybrid MR sequence that plays out the CEST preparation period and can be combined with any existing readout module. Results: The exact definition of the CEST preparation period, in combination with the flexible simulation, leads to a good match between simulations and measurements. The standard allowed finding consensus on three amide proton transfer–weighted protocols that could be compared in healthy subjects and a tumor patient. In addition, we could show coherent multisite results for a sophisticated CEST method, highlighting the benefits regarding protocol sharing and reproducibility. Conclusion: With Pulseq‐ CEST, we provide a straightforward approach to standardize, share, simulate, and measure different CEST preparation schemes, which are inherently completely defined. Abstract : Click here for author‐reader discussions